Fracture load of ceramic crowns supported by some novel anchoring dental systems - Isil Cekic Nagas; Emre Nagas; Ferhan Egilmez; Gulfem Ergun; Pekka Vallittu; Lippo Lassila (Gazi University, 2018)
Objective: This study aimed to evaluate the fracture load of endocrown restorations and fiber-reinforced composites (FRCs) fabricated through computer-aided design/computer-aided manufacturing (CAD-CAM) for post-cores of anterior teeth. Materials and Method: Forty post-core-supported crowns and endocrowns were fabricated through CAD-CAM on a canine root zirconia model (Ice Zirconia, ZirkonZahn GmBH, Bruneck, Italy). The static load-bearing capacity was measured on the following restoration groups: Group 1: zirconia crown (Prettau anterior, ZirkonZahn GmBH) retained with CAD-CAM one-piece FRC post-core crown system (experimental CAD-CAM FRC block); Group 2: zirconia crown (Prettau anterior) retained with FRC post (GC Corp., Tokyo, Japan) with discontinuous fiber composite (EverX posterior, GC Corp) core; Group 3: zirconia endocrown (Prettau anterior); and Group 4: lithium disilicate ceramic endocrown (IPS e.max CAD, Ivoclar Vivadent AG, Schaan, Liechtenstein) (n = 10/per group). After the adhesive cementation of crowns/endocrowns to the zirconia root model, a load was applied at 45° to the long axis of the teeth and measured using a universal testing machine. The fracture modes were visually examined. The statistical analyses were performed using one-way ANOVA and Tukey post-hoc tests (p < 0.05). Results: The fracture load significantly differed among the groups (p < 0.05) and was ranked as follows: Group 3 (1168 ± 141 N) > Group 4 (721 ± 96 N) ≥ Group 1 (680 ± 86 N) > Group 2 (534 ± 36 N). Conclusion: Endocrown monoblock restorations can be used as an alternative to fiber-reinforced post-core supported crown restorations.